The concept of objects of civil turnover (Bulletin of Kharkiv National University of Internal Affairs, 2022)
In the conditions of the current world crisis, the urgent need for the further development of Ukraine in the conditions of a market economy and its economic integration with the European Union, the isues of legal regulation of civil turnover are gaining relevance. To solve them, it is necessary to define the concept of the object of civil turnover, because, as it is rightly noted in the legal literature, it is important for a lawyer to understand not only whether a certain substrate is an object of civil rights, but also whether it is an object civil turnover. The first allows to determine the content of the legal relationship that could be formed in relation to the corresponding good. The second makes it possible to determine the range of circumstances that allow or prevent the transition, transfer, alienation of such goods in society.The purpose of the study is to determine the objects of civil turnover. Methodologically, the very concept of civil turnover was considered, on the basis of which its object was determined. With the help of such a method of scientific knowledge as a conclusion by analogy, it was established that the object of civil turnover and the object of legal succession are different legal phenomena. The result of the study is the definition of the objects of civil turnover and the establishment of their distinctive features from other, similar concepts. It was determined that every object of civil turnover is an object of civil law, and vice versa, every object of civil law is an object of civil turnover, thereby questioning the truth of the popular saying "the object of civil rights cannot be that, which is not defensive.It was established that the object of turnover is precisely the objects of civil law. Subjective rights (obligations) can be considered objects of civil turnover only if they perform the function of objects of civil rights, that is, in the “right to right” construction. In all other cases, the dynamics of rights is a form of civil turnover. The legal form of civil turnover is implemented in the order of legal establishment or legal succession. Only the objects of the latter are subjective rights and obligations, but not objects of civil rights.
Keywords: objects of civil turnover; objects of civil rights; civil turnover; legal succession; establishment of rights; subjective rights.